A Sort of Permanence: Digital Remains and Posthuman Encounters with Death - Segerstad, Ylva Hård af; Bell, Jo; Yeshua-Katz, Daphna (Sciendo, 2022)
Digital remains, in the shape of devices and traces of digital content and interaction stored on the devices them selves and online, left behind by the deceased have come to play important parts in the lives of those who live on. With a posthumanist perspective we explore how user-driven engagement with digital remains are changing and diversifying existing practices related to loss and grieving. The digital remains can be seen to contain the "essence" of the deceased person embodied within the digital device. Based on interviews and observations gathered from the contexts of Israel, the UK and Sweden, we investigate the role of digital remains in bereavement and what implications the eventual obsolescence of these remains might have for continuing bonds. In doing so we seek to increase our understanding of the (post)human encounter with death and the human capabilities of digital remains. digital remains, posthumanism, bereavement, continuing bonds. Abstract Keywords